Profile of Life Skills of Elementary School Students Who Participate in Sports Extracurricular Activities at Public Elementary School 053 Cisitu - Zihan Maharani; Didin Budiman; Ricky Wibowo (Journal of Physical Education Health and Sport, 2025)
This study aims to examine the life skills profiles of elementary school students who participate in extracurricular sports activities, specifically futsal and pencak silat, at Public Elementary School 053 Cisitu, Bandung. Using a quantitative descriptive comparative approach, the study involved 42 students aged 11–12 years selected through total sampling. The Positive Youth Development Sustainability Scale (PYDSS) was used as the instrument, which includes six indicators: character, competence, connection, caring, confidence, and contribution. Data analysis included descriptive statistics, normality and homogeneity tests, and independent sample t-tests. The results showed that most students had high (47.6%) to very high (28.6%) life skill levels. Although the average score of futsal participants (108.80) was slightly higher than that of pencak silat participants (107.27), the difference was not statistically significant (p = 0.653). These findings suggest that both team-based and individual sports contribute positively to students’ life skill development. The study emphasizes the importance of well-designed extracurricular programs as a medium for character building and psychosocial development in basic education.